Individual differences and retrieval interference in L2 processing - Montrul, Silvina; Tanner, Darren (Bilingualism: Language and Cognition, 2017)
Cunnings’ keynote article outlines a novel approach to native/non-native differences in on-line language comprehension by proposing that L2 speakers are more susceptible to cue-based retrieval interference than natives. Cue-based, parallel access approaches to processing have been prominent in monolingual studies for around 15 years now, but have barely been applied to L2/bilingual processing. We are particularly excited about the possibilities that this approach offers for understanding L1, L2 and bilingual processing, as well as individual differences. In this commentary, we focus on two issues: 1) whether the existing evidence for cue-based retrial mechanisms in L2 processing support a deficit model, as Cunnings seems to claim, and 2) how individual differences may explain both similarities and differences in L1 and L2 processing.